Antimony-free environment-friendly flame-retardant ABS modified material and preparation method thereof

CN122917480APending Publication Date: 2026-10-16SHENZHEN BEST ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611278572.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0003]现有无卤阻燃体系虽环保,但仍存在诸多技术瓶颈:一方面,磷氮系阻燃剂与ABS基体相容性差,通常添加量需要20wt%以上才能达到理想阻燃等级,却导致冲击强度和断裂伸长率等力学性能严重劣化;另一方面,现有无卤阻燃ABS材料的耐老化性能普遍不足,阻燃剂在光热条件下易迁移析出或分解失效,导致材料使用寿命期内性能持续衰减,影响产品长期可靠性

Benefits of technology

本发明以ABS树脂为基体树脂,通过改性层状双金属氢氧化物和改性MOF基多孔碳功能化改性,配合MBS核壳粒子增韧,以及复配抗氧剂和润滑剂,各组分功能互补、协同增效,成功实现了阻燃性能、力学性能和耐老化性能的同步提升与综合平衡。其中,改性层状双金属氢氧化物通过凝聚相催化成炭、LDH二维物理阻隔和聚磷腈气相阻燃,改性MOF基多孔碳通过多孔碳纳米限域效应、氮掺杂催化成炭和聚磷酰胺气相阻燃,MBS核壳粒子通过其柔软的橡胶核有效吸收和分散冲击能量,显著弥补了无机/有机杂化填料引入对基体韧性的不利影响,使材料的刚韧平衡得以维持;抗氧剂有效抑制了材料在高温熔融加工过程中的热氧化降解,保障了加工稳定性;润滑剂改善了高填充体系的熔体流动性和脱模性,确保材料具有良好的加工窗口。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application belongs to the field of high polymer materials, and discloses a kind of antimony-free environmental protection flame-retardant ABS modified material and its preparation method, antimony-free environmental protection flame-retardant ABS modified material includes the following weight parts raw materials: ABS resin 70~90 parts, modified layered double metal hydroxide 8~16 parts, modified MOF-based porous carbon 4~8 parts, MBS resin 3~5 parts, ABS-g-MAH 2~4 parts, antioxidant 0.3~0.6 parts, lubricant 0.5~1.5 parts;The application uses ABS resin as matrix resin, is modified by modified layered double metal hydroxide and modified MOF-based porous carbon functionalization, cooperates MBS core-shell particle toughening, and compound antioxidant and lubricant, the function of each component is complementary, synergistic effect, successfully realized the synchronous promotion and comprehensive balance of flame-retardant performance, mechanical property and ageing resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer materials technology, specifically relating to an antimony-free, environmentally friendly, flame-retardant modified ABS material and its preparation method. Background Technology

[0002] Acrylonitrile-butadiene-styrene copolymer (ABS resin) boasts excellent overall performance and good processing adaptability, making it widely used in electronic and electrical appliance housings, automotive interior parts, and office equipment housings. However, ABS contains a large amount of hydrocarbon elements in its molecular structure, with a limiting oxygen index of only about 18%, classifying it as a highly flammable material. During combustion, the flame spreads rapidly and releases large amounts of black smoke and toxic gases, severely limiting its application in high-end fields such as electronics, electrical appliances, and rail transportation, where flame retardancy requirements are stringent. Currently, ABS flame retardant modification is mainly divided into halogen-based flame retardant systems and phosphorus-nitrogen-based halogen-free flame retardant systems. Traditional halogen-based flame retardants are often used synergistically with antimony trioxide, achieving high flame retardant efficiency, but releasing large amounts of toxic hydrogen halide gases and fumes during combustion, and antimony compounds possess biological toxicity.

[0003] While existing halogen-free flame retardant systems are environmentally friendly, they still face several technical bottlenecks. On the one hand, phosphorus-nitrogen flame retardants have poor compatibility with the ABS matrix, typically requiring an addition of over 20 wt% to achieve the ideal flame retardant rating, which leads to severe degradation of mechanical properties such as impact strength and elongation at break. On the other hand, existing halogen-free flame-retardant ABS materials generally suffer from insufficient aging resistance; flame retardants are prone to migration, precipitation, or decomposition under photothermal conditions, resulting in continuous performance degradation throughout the material's lifespan and affecting long-term product reliability. Furthermore, although attempts have been made to use inorganic nanoparticles as flame retardant synergists, these particles readily aggregate in the ABS matrix, exhibiting poor dispersibility and weak interfacial bonding, resulting in limited synergistic effects. Therefore, developing an antimony-free, halogen-free, environmentally friendly flame-retardant ABS modified material with high flame retardancy at low addition levels, combined with excellent mechanical properties and long-term aging resistance, has become a pressing technical challenge in this field. Summary of the Invention

[0004] To address the shortcomings mentioned in the background art, the present invention aims to provide an antimony-free, environmentally friendly, flame-retardant modified ABS material and its preparation method. Using ABS resin as the base resin, the material is functionalized by modified layered bimetallic hydroxides and modified MOF-based porous carbon, combined with MBS core-shell particle toughening, and compounded with antioxidants and lubricants. The components complement each other and synergistically enhance each other's functions, successfully achieving simultaneous improvement and comprehensive balance of flame retardant performance, mechanical properties, and aging resistance.

[0005] The objective of this invention can be achieved through the following technical solutions: An antimony-free, environmentally friendly, flame-retardant modified ABS material comprises the following raw materials in parts by weight: 70-90 parts ABS resin, 8-16 parts modified layered bimetallic hydroxide, 4-8 parts modified MOF-based porous carbon, 3-5 parts MBS resin, 2-4 parts ABS-g-MAH, 0.3-0.6 parts antioxidant, and 0.5-1.5 parts lubricant; Modified layered bimetallic hydroxides are core-shell structured nanomaterials with cerium-doped zinc-aluminum layered bimetallic hydroxides as the core and polyphosphazene shells polymerized in situ. Modified MOF-based porous carbon is obtained by high-temperature carbonization of titanium-based MOF to obtain nitrogen-doped porous carbon, and then polyphosphoramide functional segments are introduced through surface grafting polymerization.

[0006] Preferably, the antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 2:1.

[0007] Preferably, the lubricant is one or more of zinc stearate, magnesium stearate, ethylene bis-stearamide, polyethylene wax, and pentaerythritol stearate.

[0008] Preferably, the method for preparing the modified layered bimetallic hydroxide includes the following steps: (1) Dissolve zinc nitrate hexahydrate, aluminum nitrate nonahydrate and cerium nitrate hexahydrate in deionized water to obtain a salt solution. Dissolve sodium hydroxide and sodium carbonate in deionized water to obtain an alkaline solution. At room temperature and with vigorous stirring, slowly add the alkaline solution to the salt solution to cause a coprecipitation reaction. Transfer the resulting slurry to a hydrothermal reactor and crystallize at 110°C for 22-26 hours. After natural cooling, wash repeatedly with deionized water until neutral and dry under vacuum to obtain cerium-doped layered bimetallic hydroxide. (2) Cerium-doped layered bimetallic hydroxide was ultrasonically dispersed in tetrahydrofuran. Hexachlorocyclotriphosphazene and 4,4'-dihydroxydiphenyl sulfone were added to the above dispersion. Triethylamine was slowly added dropwise under nitrogen protection. The mixture was stirred in a water bath at 50°C for 4-8 hours. After the reaction was completed, the mixture was centrifuged and washed with THF and deionized water 2-4 times alternately. The product was then dried under vacuum to obtain the modified layered bimetallic hydroxide.

[0009] Preferably, the mass ratio of zinc nitrate hexahydrate, aluminum nitrate nonahydrate, and cerium nitrate hexahydrate is 8~10:4~6:1.

[0010] Preferably, the mass ratio of cerium-doped layered bimetallic hydroxide, hexachlorocyclotriphosphazene, and 4,4'-dihydroxydiphenyl sulfone is 3~4:1~2:1.

[0011] Preferably, the method for preparing modified MOF-based porous carbon includes the following steps: A. Dissolve terephthalic acid and tetraisopropyl titanate in a mixed solution of N,N-dimethylformamide and methanol, stir until completely dissolved, react at 150°C for 18-22 h, cool naturally, collect the white solid by centrifugation, wash 3-5 times with N,N-dimethylformamide and anhydrous methanol, and activate the product in a vacuum drying oven at 150°C for 10-14 h to obtain metal-organic framework powder; B. Place the metal-organic framework powder in a tube furnace and heat it to 800°C at a heating rate of 5°C / min under the protection of nitrogen or argon atmosphere. Carbonize it at 800°C for 1.5 to 2.5 hours. After naturally cooling to room temperature, take out the black powder to obtain nitrogen-doped porous carbon. C. Nitrogen-doped porous carbon was ultrasonically dispersed in anhydrous ethanol. Phosphorus oxychloride and ethylenediamine were added dropwise to the dispersion under an ice-water bath and vigorous stirring. After the addition was complete, the ice bath was removed, and the reaction was continued at room temperature for 3-5 hours. After the reaction was completed, the mixture was centrifuged, washed 3-5 times with anhydrous ethanol and deionized water, and vacuum dried to obtain modified MOF-based porous carbon.

[0012] Preferably, the mass ratio of terephthalic acid to tetraisopropyl titanate is 1 to 3:1.

[0013] Preferably, the mass ratio of nitrogen-doped porous carbon, phosphorus oxychloride, and triethylamine is 1~2:2~3:1.

[0014] A method for preparing an antimony-free, environmentally friendly, flame-retardant modified ABS material includes the following steps: S1. ABS resin is dried in a forced-air drying oven at 80~90℃ for 4~6h. Modified layered bimetallic hydroxide and modified MOF-based porous carbon are dried in a vacuum oven at 60℃ for 10~14h. After weighing each raw material according to the formula, they are mixed in a high-speed mixer at room temperature for 5~10min to obtain the mixture. S2. Add the mixture to a twin-screw extruder and perform melt blending extrusion using a twin-screw extruder. The extrusion temperature is 190~220℃ and the screw speed is 200~300r / min. The extrudate is cooled in a water tank and granulated to obtain modified ABS plastic granules. S3. Modified ABS plastic granules are dried at 80~90℃ for 3~5 hours and then injection molded at an injection temperature of 200~230℃ and a mold temperature of 40~60℃ to obtain antimony-free environmentally friendly flame-retardant modified ABS material.

[0015] The beneficial effects of this invention are: This invention uses ABS resin as the base resin and achieves simultaneous improvement and comprehensive balance of flame retardant, mechanical properties, and aging resistance through functional modification of layered bimetallic hydroxide and modified MOF-based porous carbon, combined with toughening of MBS core-shell particles, and compounding of antioxidants and lubricants. The components complement each other and synergistically enhance each other. Specifically, the modified layered bimetallic hydroxide achieves char formation through condensed phase catalysis, LDH two-dimensional physical barrier, and gas-phase flame retardancy through polyphosphazene; the modified MOF-based porous carbon achieves char formation through porous carbon nanotube confinement effect, nitrogen doping catalysis, and gas-phase flame retardancy through polyphosphazene; and the MBS core-shell particles effectively absorb and disperse impact energy through their soft rubber core, significantly compensating for the adverse effects of inorganic / organic hybrid fillers on the toughness of the matrix and maintaining the material's rigidity-toughness balance. The antioxidant effectively inhibits thermal oxidative degradation during high-temperature melting and processing, ensuring processing stability; and the lubricant improves the melt flowability and demolding properties of the high-filler system, ensuring a good processing window for the material.

[0016] This invention relates to a modified layered bimetallic hydroxide (LDH) with a cerium-doped zinc-aluminum layered LDH nanosheet as its core. A polyphosphazene shell is coated onto the surface via in-situ polymerization, constructing a core-shell hybrid with an inorganic core-organic shell structure. Cerium ions are introduced into the LDH layers via ion exchange reactions, catalyzing cross-linking and coupling reactions of ABS molecular chains during combustion, promoting the formation of a high-density graphitized carbon layer. The polyphosphazene shell contains phosphorus and nitrogen; during combustion, phosphorus promotes char formation, and nitrogen releases non-combustible gases such as ammonia to dilute the concentration of combustible gases in the flame zone. Simultaneously, the phosphorus-containing free radicals generated by the pyrolysis of polyphosphazene effectively quench hydrogen and hydroxyl radicals in the combustion chain reaction. Therefore, the modified layered bimetallic hydroxide effectively improves the flame retardant performance of the material through a triple flame-retardant mechanism of condensed-phase catalytic char formation, physical barrier barrier, and gas-phase free radical quenching. Furthermore, the presence of cerium ions endows the material with excellent thermo-oxidative stability, capturing free radicals generated during aging and delaying molecular chain breakage.

[0017] This invention modifies MOF-based porous carbon using titanium-based MOF as a precursor. Nitrogen-doped porous carbon is obtained through high-temperature inert atmosphere carbonization, followed by interfacial polymerization to graft polyphosphoramide functional segments onto its surface. After MOF carbonization, it retains its high specific surface area and ordered pore structure. These nanopores can efficiently adsorb and capture active free radicals generated during combustion, interrupting the chain combustion reaction. Simultaneously, the NC active sites in the nitrogen-doped carbon can synergistically catalyze char formation. The polyphosphoramide segments introduced through surface grafting polymerization contain abundant phosphoramide groups. During combustion, these phosphorus-containing free radicals quench hydrogen and hydroxyl radicals in the flame zone. Furthermore, the nitrogen-containing non-combustible gases produced by their decomposition further dilute the concentration of combustible gases, exerting a highly efficient gas-phase flame retardant effect, thereby improving the flame retardant performance of the material. Additionally, the PN bonds in the polyphosphoramide segments themselves have the ability to capture peroxide free radicals, while the porous structure of MOFC can physically adsorb oxygen and free radicals. The synergistic effect of both endows the material with excellent resistance to thermo-oxidative aging.

[0018] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation

[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0020] Example 1 A method for preparing a modified layered bimetallic hydroxide includes the following steps: (1) Dissolve 11.9g zinc nitrate hexahydrate, 6.38g aluminum nitrate nonahydrate and 1.30g cerium nitrate hexahydrate in 100mL of deionized water to obtain a salt solution. Dissolve 6.4g sodium hydroxide and 2.12g sodium carbonate in 100mL of deionized water to obtain an alkaline solution. Under room temperature and vigorous stirring, slowly add the alkaline solution to the salt solution to cause a coprecipitation reaction. Transfer the resulting slurry to a hydrothermal reactor and crystallize at 110℃ for 24h. After natural cooling, wash repeatedly with deionized water until neutral and vacuum dry at 60℃ for 12h to obtain cerium-doped layered bimetallic hydroxide. (2) 5.0 g of cerium-doped layered bimetallic hydroxide was ultrasonically dispersed in 200 mL of tetrahydrofuran. 2.0 g of hexachlorocyclotriphosphazene and 1.44 g of 4,4′-dihydroxydiphenyl sulfone were added to the dispersion. Under nitrogen protection, 2.0 mL of triethylamine was slowly added dropwise. The mixture was stirred in a water bath at 50 °C for 6 h. After the reaction was completed, the mixture was centrifuged and washed three times with THF and deionized water to remove unreacted monomers and oligomers. Finally, the mixture was vacuum dried at 60 °C for 24 h to obtain the modified layered bimetallic hydroxide.

[0021] Example 2 A method for preparing modified MOF-based porous carbon includes the following steps: A. Dissolve 3.0 g of terephthalic acid and 1.6 mL of tetraisopropyl titanate in a mixed solution of 60 mL of N,N-dimethylformamide and 6 mL of methanol, stir until completely dissolved, react at 150 °C for 20 h, and after natural cooling, collect the white solid by centrifugation. Wash the solid repeatedly with N,N-dimethylformamide and anhydrous methanol several times, and activate the product in a vacuum drying oven at 150 °C for 12 h to obtain metal-organic framework powder. B. Place the metal-organic framework powder in a tube furnace and heat it to 800°C at a heating rate of 5°C / min under the protection of nitrogen or argon atmosphere. Carbonize it at 800°C for 2 hours. After naturally cooling to room temperature, take out the black powder to obtain nitrogen-doped porous carbon. C. 2.0 g of nitrogen-doped porous carbon was ultrasonically dispersed in 100 mL of anhydrous ethanol. Under ice-water bath and vigorous stirring, 2.0 mL of phosphorus oxychloride and 1.5 mL of ethylenediamine were added dropwise to the dispersion. After the addition was complete, the ice bath was removed, and the reaction was continued at room temperature for 4 h. After the reaction was completed, the mixture was centrifuged, and the product was repeatedly washed with anhydrous ethanol and deionized water to remove unreacted monomers and self-polymers. Finally, the product was vacuum dried at 60 °C for 12 h to obtain modified MOF-based porous carbon.

[0022] Example 3 An antimony-free, environmentally friendly, flame-retardant modified ABS material comprises the following raw materials in parts by weight: 70 parts ABS resin, 8 parts modified layered bimetallic hydroxide, 4 parts modified MOF-based porous carbon, 3 parts MBS resin, 2 parts ABS-g-MAH, 0.2 parts antioxidant 1010, 0.1 parts antioxidant 168, 0.4 parts zinc stearate, and 0.1 parts ethylene bis-stearamide; the modified layered bimetallic hydroxide was prepared in Example 1; and the modified MOF-based porous carbon was prepared in Example 2.

[0023] The preparation method of the above-mentioned antimony-free, environmentally friendly, flame-retardant modified ABS material includes the following steps: S1. ABS resin was dried in an 80℃ forced-air drying oven for 6 hours. Modified layered bimetallic hydroxide and modified MOF-based porous carbon were dried in a vacuum oven at 60℃ for 10 hours. After weighing each raw material according to the formula, they were mixed in a high-speed mixer at room temperature for 10 minutes to obtain the mixture. S2. Add the mixture to a twin-screw extruder and perform melt blending extrusion using a twin-screw extruder. The extrusion temperature is 190~220℃ and the screw speed is 300r / min. The extrudate is cooled in a water tank and granulated to obtain modified ABS plastic granules. S3. Modified ABS plastic granules are dried at 80℃ for 5 hours and then injection molded at an injection temperature of 200~230℃ and a mold temperature of 60℃ to obtain the antimony-free, environmentally friendly, flame-retardant modified ABS material.

[0024] Example 4 An antimony-free, environmentally friendly, flame-retardant modified ABS material comprises the following raw materials in parts by weight: 90 parts ABS resin, 16 parts modified layered bimetallic hydroxide, 8 parts modified MOF-based porous carbon, 5 parts MBS resin, 4 parts ABS-g-MAH, 0.4 parts antioxidant 1010, 0.2 parts antioxidant 168, 0.8 parts magnesium stearate, 0.2 parts ethylene bis-stearamide, and 0.5 parts polyethylene wax; the modified layered bimetallic hydroxide was prepared in Example 1; the modified MOF-based porous carbon was prepared in Example 2.

[0025] The preparation method of the above-mentioned antimony-free, environmentally friendly, flame-retardant modified ABS material includes the following steps: S1. ABS resin was dried in a 90℃ forced-air drying oven for 4 hours. Modified layered bimetallic hydroxide and modified MOF-based porous carbon were dried in a vacuum oven at 60℃ for 14 hours. After weighing each raw material according to the formula, they were mixed at room temperature for 5 minutes in a high-speed mixer to obtain the mixture. S2. Add the mixture to a twin-screw extruder and perform melt blending extrusion using a twin-screw extruder. The extrusion temperature is 190~220℃ and the screw speed is 300r / min. The extrudate is cooled in a water tank and granulated to obtain modified ABS plastic granules. S3. Modified ABS plastic granules are dried at 80℃ for 5 hours and then injection molded at an injection temperature of 200~230℃ and a mold temperature of 60℃ to obtain the antimony-free, environmentally friendly, flame-retardant modified ABS material.

[0026] Example 5 An antimony-free, environmentally friendly, flame-retardant modified ABS material comprises the following raw materials in parts by weight: 80 parts ABS resin, 12 parts modified layered bimetallic hydroxide, 6 parts modified MOF-based porous carbon, 4 parts MBS resin, 3 parts ABS-g-MAH, 0.3 parts antioxidant 1010, 0.15 parts antioxidant 168, 0.6 parts zinc stearate, 0.2 parts ethylene bis-stearamide, and 0.2 parts pentaerythritol stearate; the modified layered bimetallic hydroxide was prepared in Example 1; the modified MOF-based porous carbon was prepared in Example 2.

[0027] The preparation method of the above-mentioned antimony-free, environmentally friendly, flame-retardant modified ABS material includes the following steps: S1. ABS resin was dried in an 85℃ forced-air drying oven for 5 hours. Modified layered bimetallic hydroxide and modified MOF-based porous carbon were dried in a vacuum oven at 60℃ for 12 hours. After weighing each raw material according to the formula, they were mixed in a high-speed mixer at room temperature for 8 minutes to obtain the mixture. S2. Add the mixture to a twin-screw extruder and perform melt blending extrusion using a twin-screw extruder. The extrusion temperature is 190~220℃ and the screw speed is 250r / min. The extrudate is cooled in a water tank and granulated to obtain modified ABS plastic granules. S3. The modified ABS plastic granules are dried at 85℃ for 4 hours and then injection molded at an injection temperature of 200~230℃ and a mold temperature of 50℃ to obtain the antimony-free environmentally friendly flame-retardant modified ABS material.

[0028] Comparative Example 1 An antimony-free, environmentally friendly, flame-retardant modified ABS material comprises the following raw materials in parts by weight: 80 parts ABS resin, 6 parts modified MOF-based porous carbon, 4 parts MBS resin, 3 parts ABS-g-MAH, 0.3 parts antioxidant 1010, 0.15 parts antioxidant 168, 0.6 parts zinc stearate, 0.2 parts ethylene bis-stearamide, and 0.2 parts pentaerythritol stearate; the modified MOF-based porous carbon is prepared in Example 2.

[0029] The preparation method of the above-mentioned antimony-free environmentally friendly flame-retardant modified ABS material is the same as that in Example 5, except that no modified layered bimetallic hydroxide is added to the raw materials in step S1.

[0030] Comparative Example 2 An antimony-free, environmentally friendly, flame-retardant modified ABS material comprises the following raw materials in parts by weight: 80 parts ABS resin, 12 parts modified layered bimetallic hydroxide, 4 parts MBS resin, 3 parts ABS-g-MAH, 0.3 parts antioxidant 1010, 0.15 parts antioxidant 168, 0.6 parts zinc stearate, 0.2 parts ethylene bis-stearamide, and 0.2 parts pentaerythritol stearate; the modified layered bimetallic hydroxide is prepared in Example 1.

[0031] The preparation method of the above-mentioned antimony-free environmentally friendly flame-retardant modified ABS material is the same as that in Example 5, except that modified MOF-based porous carbon is not added to the raw materials in step S1.

[0032] Performance testing To characterize the performance-enhancing effects of modified layered bimetallic hydroxide and modified MOF-based porous carbon on the materials, the antimony-free environmentally friendly flame-retardant ABS modified materials prepared in Examples 3-5 and Comparative Examples 1 and 2 were subjected to the following performance tests: (1) Flame retardant performance test Limiting oxygen index (LOI), refer to GB / T 2406.2-2009, use an oxygen index tester, sample size 150mm×10mm×4mm, place the sample vertically in a transparent combustion tube, control the nitrogen-oxygen mixture flow rate to (40±2)mm / s, use the top ignition method, adjust the oxygen concentration downward, and observe the lowest oxygen concentration when the sample extinguishes within 3 minutes or the burning length does not exceed 50mm; Vertical flammability rating (UL-94), refer to GB / T 2408-2021, sample size 125mm×13mm×1.6mm, the sample is held vertically, and a Bunsen burner (flame height 20±1mm) is used to ignite it twice, each lasting 10 seconds, and the afterflame time (t1) of the first time, the afterflame time (t2) of the second time and the afterburn time (t3) are recorded, and it is observed whether the cotton below is ignited by the dripping material, and the vertical flammability rating is evaluated. (2) Mechanical property testing For tensile strength, refer to GB / T 1040.2-2022. Use type I dumbbell-shaped specimens with a length ≥150mm. Use a universal testing machine, place the specimen in the fixture, and apply axial tension at a constant rate of 5 mm / min until the specimen breaks. Calculate the tensile strength (MPa). Notched impact strength was determined according to GB / T 1843-2008. The specimen size was 80mm × 10mm × 4mm, with a V-notch depth of 2.54mm. A cantilever beam impact testing machine was used, with a 2.75J pendulum. One end of the specimen was fixed, and an impact load was applied to the back of the V-notch at the other end, causing it to break in one blow. The notched impact strength (kJ / m²) was calculated. 2 ); (3) Aging resistance test Impact strength retention rate, referring to GB / T 16422.2-2022, involves placing the notched impact strength specimens used in the mechanical property test in a xenon arc lamp aging test chamber with an irradiance of 0.51 W / m². 2@340nm, blackboard temperature set to 65±3℃, chamber temperature set to 38℃, relative humidity set to 50%, light-spray cycle mode adopted (spraying for 18 minutes every 2 hours), cumulative exposure for 1000 hours, notched impact strength tested before and after aging, and notched impact strength retention rate (%) after aging calculated. (4) Heat resistance Heat distortion temperature (HDT), referring to GB / T 1634.1-2025, with a sample size of 80mm×10mm×4mm, the standard bending sample is placed in the deformation measuring device, immersed in heat transfer oil, a surface stress of 1.82 MPa is applied, and the temperature is increased at a rate of 120℃ / h. The temperature at which the bending deformation at the midpoint of the sample reaches the specified value is recorded as the heat distortion temperature (℃). The results are shown in Table 1 below.

[0033] Table 1 Performance Test Results of Antimony-Free Environmentally Friendly Flame-Retardant Modified ABS Materials

[0034] As can be seen from the data in Table 1, the flame retardant properties of Examples 3-5 are excellent. With the increase of the amount of modified layered bimetallic hydroxide and modified MOF-based porous carbon, the flame retardant properties show a continuous and significant upward trend. The flame retardant properties of the materials in Comparative Examples 1 and 2 are lower than those in Example 5, indicating that the modified layered bimetallic hydroxide and modified MOF-based porous carbon have a significant synergistic effect. When used alone, the flame retardant efficiency is limited, but when the two are used in combination, the flame retardant performance is greatly improved.

[0035] During combustion, modified layered bimetallic hydroxides release cerium ions (Ce). 3+ The catalytic cross-coupling reaction of ABS molecular chains promotes cross-linking and char formation, creating a dense char layer on the material surface. This char layer acts as a physical barrier, effectively blocking heat transfer and oxygen diffusion, and inhibiting further pyrolysis and combustion of the internal materials. The two-dimensional layered structure of the layered bimetallic hydroxide releases interlayer water and CO2 during combustion, diluting the concentration of combustible gases. Furthermore, its layered structure forms a physical barrier layer on the material surface. This layered stacking effect is similar to the barrier mechanism of nano-clay, significantly slowing down the rate of heat and oxygen transfer. The polyphosphazene shell contains phosphorus and nitrogen. During combustion, phosphorus promotes the char formation reaction; nitrogen releases non-combustible gases such as NH3, diluting the concentration of combustible gases in the flame zone. Simultaneously, the PO· / PO2· free radicals generated by the pyrolysis of polyphosphazene can capture H· and OH· free radicals in the combustion chain reaction, interrupting the combustion reaction.

[0036] Modified MOF-based porous carbon possesses a high specific surface area and an ordered pore structure. These nanopores can adsorb and capture active free radicals generated during combustion, interrupting the chain combustion reaction and thus reducing the combustion rate and heat release rate. Organic ligands introduce nitrogen doping during high-temperature carbonization, forming NC active sites. These active sites can catalyze the char formation reaction and adsorb acidic degradation products, enhancing the density and thermal stability of the char layer. The functional segments on the surface of polyphosphoramide release phosphorus-containing free radicals (PO· / PO2·) during combustion, which can effectively quench H· and OH· free radicals in the flame zone, interrupting the chain reaction of combustion and playing a gas-phase flame-retardant role.

[0037] In Examples 3-5, with the increase of modified layered bimetallic hydroxide and modified MOF-based porous carbon content, the tensile strength of the material showed a very gradual decreasing trend. This indicates that after surface functionalization, the two additives have good interfacial bonding with the ABS matrix, avoiding the agglomeration of inorganic particles and ensuring that nanoparticles are uniformly dispersed in the matrix, reducing the deterioration of mechanical properties. The material did not develop severe stress concentration points due to the introduction of fillers, and its rigidity was well preserved. The notched impact strength showed a relatively obvious decreasing trend, but this loss was effectively compensated by the directional toughening compensation of MBS core-shell particles.

[0038] The impact strength retention rates of the materials in Examples 3-5 all reached over 78%, while the impact strength retention rates of Comparative Example 1 were only 62% and Comparative Example 2 were 68%, both significantly lower than that of Example 5, indicating that both additives possess anti-aging properties. The catalytic stabilizing effect of cerium ions in the modified layered bimetallic hydroxide can inhibit the thermo-oxidative degradation of ABS. The porous structure of the modified MOF-based porous carbon can adsorb and quench free radicals, inhibiting oxidative degradation during photothermal aging. The PN bonds in the polyphosphoramide segments can capture peroxide free radicals, terminating the auto-oxidation chain reaction and endowing the material with excellent thermo-oxidative aging resistance.

[0039] In Examples 3-5, the heat distortion temperature of the materials showed a steady upward trend with the introduction of modified layered bimetallic hydroxide and modified MOF-based porous carbon. This is because the uniformly dispersed nanoparticles restricted the thermal movement of ABS molecular chains near the glass transition temperature, giving the materials higher resistance to heat distortion.

[0040] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0041] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. An antimony-free, environmentally friendly, flame-retardant modified ABS material, characterized in that, The raw materials include the following parts by weight: 70-90 parts ABS resin, 8-16 parts modified layered bimetallic hydroxide, 4-8 parts modified MOF-based porous carbon, 3-5 parts MBS resin, 2-4 parts ABS-g-MAH, 0.3-0.6 parts antioxidant, and 0.5-1.5 parts lubricant; The modified layered bimetallic hydroxide is a core-shell structured nanomaterial with cerium-doped zinc-aluminum layered bimetallic hydroxide as the core and polyphosphazene shells polymerized in situ. The modified MOF-based porous carbon is obtained by high-temperature carbonization of titanium-based MOF to obtain nitrogen-doped porous carbon, and then polyphosphoramide functional segments are introduced through surface grafting polymerization.

2. The antimony-free, environmentally friendly, flame-retardant modified ABS material according to claim 1, characterized in that, The antioxidant is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 2:

1.

3. The antimony-free, environmentally friendly, flame-retardant modified ABS material according to claim 1, characterized in that, The lubricant is one or more of zinc stearate, magnesium stearate, ethylene bis-stearamide, polyethylene wax, and pentaerythritol stearate.

4. The antimony-free, environmentally friendly, flame-retardant modified ABS material according to claim 1, characterized in that, The method for preparing the modified layered bimetallic hydroxide includes the following steps: (1) Dissolve zinc nitrate hexahydrate, aluminum nitrate nonahydrate and cerium nitrate hexahydrate in deionized water to obtain a salt solution. Dissolve sodium hydroxide and sodium carbonate in deionized water to obtain an alkaline solution. At room temperature and with vigorous stirring, slowly add the alkaline solution to the salt solution to cause a coprecipitation reaction. Transfer the resulting slurry to a hydrothermal reactor and crystallize at 110°C for 22-26 hours. After natural cooling, wash repeatedly with deionized water until neutral and dry under vacuum to obtain cerium-doped layered bimetallic hydroxide. (2) Cerium-doped layered bimetallic hydroxide was ultrasonically dispersed in tetrahydrofuran. Hexachlorocyclotriphosphazene and 4,4'-dihydroxydiphenyl sulfone were added to the dispersion. Triethylamine was slowly added dropwise under nitrogen protection. The mixture was stirred in a water bath at 50°C for 4-8 hours. After the reaction was completed, the mixture was centrifuged and washed with THF and deionized water 2-4 times alternately. The product was then dried under vacuum to obtain the modified layered bimetallic hydroxide.

5. The antimony-free, environmentally friendly, flame-retardant modified ABS material according to claim 4, characterized in that, The mass ratio of zinc nitrate hexahydrate, aluminum nitrate nonahydrate, and cerium nitrate hexahydrate is 8~10:4~6:

1.

6. The antimony-free, environmentally friendly, flame-retardant modified ABS material according to claim 4, characterized in that, The mass ratio of the cerium-doped layered bimetallic hydroxide, hexachlorocyclotriphosphazene, and 4,4'-dihydroxydiphenyl sulfone is 3~4:1~2:

1.

7. The antimony-free, environmentally friendly, flame-retardant modified ABS material according to claim 1, characterized in that, The method for preparing the modified MOF-based porous carbon includes the following steps: A. Dissolve terephthalic acid and tetraisopropyl titanate in a mixed solution of N,N-dimethylformamide and methanol, stir until completely dissolved, react at 150°C for 18-22 h, cool naturally, collect the white solid by centrifugation, wash 3-5 times with N,N-dimethylformamide and anhydrous methanol, and activate the product in a vacuum drying oven at 150°C for 10-14 h to obtain metal-organic framework powder; B. Place the metal-organic framework powder in a tube furnace and heat it to 800°C at a heating rate of 5°C / min under the protection of nitrogen or argon atmosphere. Carbonize it at 800°C for 1.5 to 2.5 hours. After naturally cooling to room temperature, take out the black powder to obtain nitrogen-doped porous carbon. C. Nitrogen-doped porous carbon was ultrasonically dispersed in anhydrous ethanol. Phosphorus oxychloride and ethylenediamine were added dropwise to the dispersion under an ice-water bath and vigorous stirring. After the addition was complete, the ice bath was removed, and the reaction was continued at room temperature for 3-5 hours. After the reaction was completed, the mixture was centrifuged, washed 3-5 times with anhydrous ethanol and deionized water, and vacuum dried to obtain modified MOF-based porous carbon.

8. The antimony-free, environmentally friendly, flame-retardant modified ABS material according to claim 7, characterized in that, The mass ratio of terephthalic acid to tetraisopropyl titanate is 1~3:

1.

9. The antimony-free, environmentally friendly, flame-retardant modified ABS material according to claim 7, characterized in that, The mass ratio of nitrogen-doped porous carbon, phosphorus oxychloride, and triethylamine is 1~2:2~3:

1.

10. The preparation method of the antimony-free environmentally friendly flame-retardant modified ABS material according to any one of claims 1 to 9, characterized in that, Includes the following steps: S1. ABS resin is dried in a forced-air drying oven at 80~90℃ for 4~6h. Modified layered bimetallic hydroxide and modified MOF-based porous carbon are dried in a vacuum oven at 60℃ for 10~14h. After weighing each raw material according to the formula, they are mixed in a high-speed mixer at room temperature for 5~10min to obtain the mixture. S2. Add the mixture to a twin-screw extruder and perform melt blending extrusion using a twin-screw extruder. The extrusion temperature is 190~220℃ and the screw speed is 200~300r / min. The extrudate is cooled in a water tank and granulated to obtain modified ABS plastic granules. S3. The modified ABS plastic granules are dried at 80~90℃ for 3~5 hours and then injection molded at an injection temperature of 200~230℃ and a mold temperature of 40~60℃ to obtain the antimony-free environmentally friendly flame-retardant modified ABS material.